Troubleshooting Guide to Expressing Intrinsically Disordered Proteins for Use in NMR Experiments - Graether, Steffen P. (Frontiers in Molecular Biosciences, 2019)
Intrinsically disordered proteins (IDPs) represent a structural class of proteins that do not have a well-defined, 3D fold in solution, and often have little secondary structure. To characterize their function and molecular mechanism, it is helpful to examine their structure using nuclear magnetic resonance (NMR), which can report on properties such as residual structure (at both the secondary and tertiary levels), ligand binding affinity, and the effect of ligand binding on IDP structure. This brief review reports on the common problems and decisions that are involved when preparing a disordered protein for NMR studies. The paper covers gene design, expression host choice, protein purification, and the initial NMR experiments that are performed. While many of these steps are essentially identical to those used for ordered proteins, there are several, key differences, including the need for protein labeling with stable isotopes, the extreme sensitivity of IDPs to proteolytic cleavage, and the ability to use denaturing conditions without having to refold the protein. After successful purification, characterization by NMR can be done using the standard 15N-heteronuclear single quantum coherence (15N-HSQC) experiment, or the newer CON series of experiments that have been optimized for disordered proteins.